2003
DOI: 10.1046/j.1365-2257.2003.00516.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential counting of blood leukocytes using automated microscopy and a decision support system based on artificial neural networks - evaluation of DiffMasterTM Octavia

Abstract: The morphological appearance of blood cells has an established association to clinical conditions. A novel system, DiffMaster Octavia for differential counting of blood leukocytes, has been evaluated. The system consisted of a microscope, 3-chip color charge coupled device (CCD) camera, automated motorized stage holder, electronic hardware for motor and light control and software for automatic cell location and image processing for preclassification of blood cells using artificial neural networks. The DiffMast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 9 publications
4
40
0
Order By: Relevance
“…In this study we adapted the system to accurately determine research parameters reflecting and describing the relative position of M, PMN and total leukocytes based on fluorescence intensity of intracellular NA and protein material, side scatter for granularity and impedance count for volume or shape change depending on total lipid membrane amount. All findings were compared with and correlated to established methods like microscopic morphological cell diagnostic by pattern recognition (27), cytokine production and release (TNF-a and IL-8) and intracellular myeloperoxidase concentration in order to establish the method as a standardized and reproducible routine procedure, to understand the functional state and activity of M and PMN, the defense cells of the human innate immune system. The interpretation of the functional state or activation of M and PMN by simple means of analyser research parameters has been investigated by in vitro experiments with easily obtainable, EDTA anticoagulated whole blood samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we adapted the system to accurately determine research parameters reflecting and describing the relative position of M, PMN and total leukocytes based on fluorescence intensity of intracellular NA and protein material, side scatter for granularity and impedance count for volume or shape change depending on total lipid membrane amount. All findings were compared with and correlated to established methods like microscopic morphological cell diagnostic by pattern recognition (27), cytokine production and release (TNF-a and IL-8) and intracellular myeloperoxidase concentration in order to establish the method as a standardized and reproducible routine procedure, to understand the functional state and activity of M and PMN, the defense cells of the human innate immune system. The interpretation of the functional state or activation of M and PMN by simple means of analyser research parameters has been investigated by in vitro experiments with easily obtainable, EDTA anticoagulated whole blood samples.…”
Section: Discussionmentioning
confidence: 99%
“…The 200-cell leukocyte differential count was performed by standardized automated image analysis (27) with preclassification (DiffMaster DM 96 from CellaVision AB, Sweden). After automated preclassification of segmented neutrophils, monocytes, lymphocytes, eosinophils and basophils white blood cells were manually classified into activated cell type categories ( Fig.…”
Section: Microscopic Pattern Recognition Morphological Cellmentioning
confidence: 99%
“…In general, the performance of the automatic classification declines with increasing abnormality/immaturity of the cells. The DiffMaster TM Octavia has been validated against conventional microscopy by an extended evaluation of 322 routine specimens following the NCCLS-H20A protocol (10).…”
Section: Microscopymentioning
confidence: 99%
“…7 It was previously shown that a DM system, using several advanced mathematical algorithms, is capable of correct classification of leukocytes in peripheral blood and body fluid samples in relation to manual microscopic assessment of the five main peripheral blood cell categories. [3][4][5][8][9][10] An overall accuracy of 92.0% was found when the preclassification results of the DM96 (Cellavision, Lund, Sweden) were compared to those of manual assessment. 3,11 It has been shown that the classification performance of this particular system is as reliable as manual classification by …”
Section: Introductionmentioning
confidence: 99%